Predictors of expressed breast milk volume in mothers expressing milk for their preterm infant. Issue 6 (2nd March 2016) - Fewtrell, M S; Kennedy, K; Ahluwalia, J S; Nicholl, R; Lucas, A; Burton, P
Abstract : Background: An understanding of predictors of breast milk production may enable the provision of better advice and support to mothers with preterm infants who may need to express milk for long periods. Objective: To investigate factors predicting the amount of milk expressed by mothers for their preterm infant (1) during the first 10 days and (2) during the infant's whole hospital stay. Methods: 62 mothers with preterm infants <34 weeks who participated in a randomised trial comparing two breast pumps completed 10-day diaries including weight of milk expressed and questionnaires giving their opinion of the breast pump; 47 mothers provided data on milk expression up to the infant's hospital discharge. Results: Significant predictors of 10-day milk weight in multivariate models were the number of episodes of 'breast feeding' (17 g (95% CI 8 to 26, p=0.001) increase per episode), the use of double versus single pumping (109 (31–186, p=0.007) g/day more) and the number of complete daily records (17 (1–33, p=0.04) g increase/day). Significant multivariate predictors of total milk production were double versus single pumping (491 (55) mL/day vs 266 (44) mL/day), expressing 500 mL/day by day 10 (525 (53) mL/day vs 232 (43) mL/day) and a higher score for breast pump 'comfort' (best=489 (39) mL/day, middle=335 (57) mL/day, worst=311 (78) mL/day). Conclusions: These results suggest that relatively simple, modifiable factors can favourably impact milk production in the neonatal intensive care unit setting and emphasise the importance of double pumping, early establishment of milk production and design features of the breast pump that promote comfort. Trial registration number: NCT00887991.